Lower academic performance among children with perinatal HIV exposure in Botswana - Kathleen M. Powis; Lesedi Lebanna; Sara Schenkel; Gosego Masasa; Samuel W. Kgole; Martha Ngwaca; Coulson Kgathi; Paige L. Williams; Amy L. Slogrove; Roger L. Shapiro; Shahin Lockman; Mompati O. Mmalane; et al. (Journal of the International AIDS Society, 2023)
Abstract Introduction Studies have reported a higher risk of suboptimal neurodevelopment among children who are HIV‐exposed uninfected (HEU) compared to children HIV‐unexposed uninfected (HUU). Actual academic performance among school‐aged children by HIV exposure status has not been studied. Methods Academic performance in Mathematics, Science, English, Setswana and overall among children enrolled in the Botswana‐based FLOURISH study who were attending public primary school and ranging in age from 7.1 to 14.6 years were compared by HIV exposure status using a Cochran‐Mantel‐Haenszel test. Lower academic performance was defined as a grade of “C” or lower (≤60%). Unadjusted and adjusted logistic regression models were fit to assess for an association between HIV exposure and lower academic performance. Results Between April 2021 and December 2022, 398 children attending public primary school enrolled in the FLOURSH study, 307 (77%) were HEU. Median age was 9.4 years (IQR 8.9–10.2). Only 17.9% of children HEU were breastfeed versus 100% of children HUU. Among children HEU, 80.3% had foetal exposure to three‐drug antiretroviral treatment, 18.7% to zidovudine only and 1.0% had no antiretroviral exposure. Caregivers of children HEU were older compared to caregivers of children HUU (median 42 vs. 36 years) and more likely to have no or primary education only (15.0% vs. 1.1%). In unadjusted analyses, children HEU were more likely to have lower overall academic performance compared to their children HUU (odds ratio [OR]: 1.96 [95% confidence interval (CI): 1.16, 3.30]), and lower performance in Mathematics, Science and English. The association was attenuated after adjustment for maternal education, caregiver income, breastfeeding, low birth weight and child sex (aOR: 1.86 [95% CI: 0.78, 4.43]). Conclusions In this Botswana‐based cohort, primary school academic performance was lower among children HEU compared to children HUU. Biological and socio‐demographic factors, including child sex, appear to contribute to this difference. Further research is needed to identify modifiable contributors, develop screening tools to identify the risk of poor academic performance and design interventions to mitigate risk.